Strategi Pendidikan Islam Berbasis Moderasi Beragama Melalui Ekspresi Karnaval Budaya Pada Acara Haflah Khatmil Qur’an Pesantren Al-Asya’ariyyah Wonosobo - Robingun Suyud El Syam (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Khatmil Qur'an is a culture in various Islamic boarding schools that study the Qur'an, but the agenda of each pesantren is different in line with the tradition of the pesantren. Interestingly at the Al-Asy'ariyyah Islamic boarding school, there is a cultural carnival that presents various cultural attributes from various regions in Indonesia. So this article aims to find answers to the big question,